Corporate Social Responsibility And Company Performance - Erni Masdupi; Erni Putri Ayu; Abel Tasman (Economac: Jurnal Ilmiah Ilmu Ekonomi, 2019)
The purpose of this research is to analyze the influence of corporate social responsibility and capital structure on financial performance of high-profile company. Population in this study is all high-profile companies listed in Indonesia Stock Exchange (IDX) in the period of 2010-2015. The sample was selected by purposive sampling, hence 225 samples were obtained. This research uses secondary data from Indonesian Capital Market Directory (ICMD) and IDX companies. Structural equation modeling (SEM) is used as statistical tool. The hypothesis measurement model showed better fit as indicated by the goodness of fit indices, and also could fullfill convergent validity which reflected by the significant factor loadings. The structural model of financial perfromance also could reach better fit and it found that corporate social responsibility has a positive and significant effect on financial performance; and the capital structure has a negative and significant influnce on financial performance in high-profile companies listed on the IDX.